O velejar das embarcações maranhenses: uma narrativa sobre saberes docentes (matemáticos) de um mestre carpinteiro naval ensinados no âmbito do Estaleiro Escola - Melo, Rayane de Jesus Santos (Universidade Federal de São Carlos, 2023)
Maranhão’s origin is bonded to the sea and navigation had and still has a very important historical role in the saga of occupation of this territory, as well as in its economic and cultural development and in the habits and customs of its people. The culture of artisanal vessels mobilizes the knowledge and language of naval workers, but at the end of the 20th century and the beginning of the 21st century, it began to present a risk of disappearing, since the new generations did not show interest in learning about it. In order to preserve and value this culture and the know-how of naval workers, Luiz Phelipe Andrès founded, in 2006, the Centro Vocacional Tecnológico Estaleiro Escola, in which master ship carpenters act as teacher-trainers in the Handcrafted Vessel Construction Course and they teach the new generations knowledge and construction techniques alongside professors from the university academy. Thus, this study sought to answer two guiding questions: How did a master naval carpenter become a teacher-trainer of the Technical Course for Construction of Handcrafted Vessels? What mathematical knowledge of the master ship carpenter is taught to new apprentices within the School Shipyard? For this, it aimed to understand (mathematical) knowledge teachers used and taught by a master naval carpenter in the Course of Construction of Artisan Vessels in Maranhenses within the scope of the School Shipyard. Specifically, it sought to understand the culture of artisanal vessels in the context of Maranhão; recognize the creative processes surrounding the creation of the School Shipyard; understand the process of institutionalization of the Technical Course for the Construction of Craft Vessels; identify knowledge of educational practice revealed by a master naval carpenter that allows identifying him as a teacher-trainer; and learn about the mathematical knowledge of the master naval carpenter used in the construction of artisanal vessels and taught within the School Shipyard. The research followed the theoretical-methodological assumption of narrative research, anchored in D. Jean Clandinin and F. Michael Connelly. The research texts for this thesis were written based on data from narrative interviews; notes from the researcher's field diary; of recordings and photographs recorded during the classes of the Vessel Construction Course; of documents from the Embarcações do Maranhão Project; academic productions by Luiz Phelipe and his interviews that are available on the internet; and documentary and bibliographic sources. The constitution of the plot, which considered the three-dimensional space of the narrative research, and the interweaving of the collected data made it possible to understand experiences lived by a master naval carpenter that led him to become a teacher-trainer at the Shipyard School and that the mathematical knowledge he taught are specific to their culture and were developed in the socio-cultural context of their group. It is from this knowledge that naval workers base their interpretations about reality, their intervention projects in it, their essential habits and their everyday behaviors. Throughout the research text and reflections, it was possible to support the thesis: the performance of the master ship carpenter as a teacher-trainer and the teaching of his knowledge, specifically mathematical knowledge, allow the School Shipyard's mission to preserve, value and transmitting Maranhão's culture and art of craft craft building to new generations, does not become just a utopia.
Sailing vessels from Maranhão: a narrative about teaching knowledge (mathematics) of a master naval carpenter taught in the scope of the Estaleiro Escola.
Keywords: Saberes matemáticos; Carpinteiros navais; Pesquisa narrativa; Embarcações Artesanais; Escola Vocacional; Educação Matemática; Saberes da prática educativa; Cultura Maranhense; Mathematical knowledge; Ship carpenters; Narrative research; Craft Vessels; Vocational School; Mathematics Education; Knowledge of educational practice; Maranhão Culture; CIENCIAS HUMANAS::EDUCACAO